Optimization of In Vitro Conservation Protocol of Carica pubescens Lenne & K. Koch through Medium Concentration, Temperature and Irradiation Duration Decrease - Rahayu, Enni Suwarsi; Habibah, Noor Aini (Biosaintifika: Journal of Biology & Biology Education, 2016)
Carica pubescens Lenne & K. Koch, an endemic species in Dieng mountains, must be conserved. The in vitro conservation has been developed, but sub-culture period needs to be extended. This study aimed to obtain a more efficient in vitro conservation protocol of C. pubescens. The research was carried out experimentally by using a completely randomized factorial design with three factors, namely decreasing in storage medium concentration (75% and 50% of MS medium), temperature (4oC and 8C), and irradiation duration (8 hours/day and 16 hours/day). Shoots were kept in the storage medium for 6, 9 and 12 months, then their viability were tested by growing them in the regeneration medium. Data were analyzed by Analyses of Variance and Least Significant Difference Test. The results showed that medium concentration of 50% of MS, the temperature of 8 C, and 16 hours/day of irradiation were able to suppress the C. pubescens growth in vitro storage for six months and could maintain its viability in the regeneration medium. Based on these results the medium concentration of 50% of MS, the temperature of 8 C and 16 hours/day irradiation can be used for in vitro conservation of C. pubescens without sub-culture for six months. How to CiteRahayu, E., & Habibah, N. (2016). Optimization of In Vitro Conservation Protocol of Carica pubescens Lenne & K. Koch through Medium Concentration, Temperature and Irradiation Duration Decrease. Biosaintifika: Journal of Biology & Biology Education, 8(1), 85-93.